Examination of Dynamic Mental Constructs and their Change Regarding Phases of the Moon - Ali Sağdıç; Elvan Sahin (Journal of Science Learning, 2023)
An immense body of literature on astronomy studies has provided evidence that individuals perceive the lunar phases concept as difficult. Furthermore, many studies showed what erroneous explanations or alternative conceptions of lunar phases are. However, there is also a need to understand how individuals construct an explanation of the phases of the Moon. This paper aims to explore pre-service science teachers' construction process of their explanation regarding lunar phases via clinical interviews. The data were obtained from fourteen pre-service science teachers and analyzed, identifying their nodes and dynamic mental constructs. The results indicated that most pre-service science teachers did not organize their nodes consistent with normative scientific explanations. In addition, pre-service science teachers changed their dynamic mental construct while explaining different lunar phases, utilizing different media such as drawing and three-dimensional models, and responding to prompted questions. It was suggested that different opportunities, including technology-enriched activities regarding phases of the Moon, should be provided for pre-service science teachers to reorganize their nodes.